Attitudes and beliefs of nurses and physicians about managing sexual health in primary care: A multi‐site cross‐sectional comparative study - Juan M. Leyva‐Moral; Mariela Aguayo‐Gonzalez; Patrick A. Palmieri; Genesis Guevara‐Vasquez; Nina Granel‐Grimenez; Artur Dalfó‐Pibernat (Wiley, 2021)
Abstract Aim To understand the attitudes and beliefs of nurses and physicians about managing the sexual health of patients during office visits in primary care centres. Design A questionnaire‐based, cross‐sectional multi‐centre study. Methods The study was performed in 15 primary care centres in Barcelona (Spain), from December 2017-February 2018. Obtained data were analysed with descriptive and bivariate statistics. Results Nearly half the participants believed they should manage sexual health in primary care, but a third of them disagreed this is a priority. Participants also believed patients are not comfortable speaking with them about sex. Statistically significant differences were observed between the professions as nurses more often reported receiving sexual health questions from patients and believed they had enough knowledge to appropriately respond. Most participants wanted additional education to speak with patients more comfortably and confidently about sex.